(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdVeGfs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg cJGH GdVeGf hgh YbO TQY ddJYgO HeGd hfbhO hGdJYgO HGdeGd bO jchf Vef Ydjg ddeXehf Yfg (B.. (3hbO dG jchf agG gfG KdGKI CbSGe GdbSe GdChd aj XeGfs
(3BNQgG (B:s
(3BNQgG(B: (3ebJVi GdYbO ZjQ LjO fYe dh UQM HEQGOI GdLedI ef GdLRFjf (B.. (3GdUMI bdJ agPG UQjM aj Pdc hGdCUd ajg EfeG gh GdCUd GdPj bO CTGQ Edjg (B.. (3hdcf bO jQO Ydjg HCfg ebWhY HJdc GdCUdjf GdePchQjf GdeYJVOjf HeG YQaJg adGMX hJCed hGddg CYde hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis